Secure Virtual Machine Migration Technique using Blockchain - Shri, M. Lawanya; K, Santhi; E.Gangadevi,; S, Meenatchi. (International Journal of Psychosocial Rehabilitation, 2020)
Blockchain Technology is a dedicated chain of structured block for storing data in a Comprehensible and robust way. Cloud computing is a collection of remote servers that helps the consumers to store the data, manage and for processing the data based on pay as you go model. Virtual Machine Migration is a process of managing the virtual machines in a powerful way so that it increases the performance of the system. VM Migration over internet takes a large amount of time to migrate virtual machines to the cloud providers. It becomes mandatory for migrating virtual machines to cloud with a less amount of time, for this challenge we need load balancing. The paper discuss about how virtual machine migration takes place with the use of blockchain technology that protects the virtual machine data from malicious tampering.